The Human Face of Industrial Conflict in Post-War Japan - Gagnon, Mona-Josée (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "The Human Face of Industrial Conflict in Post-War Japan," edited by Hirosuke Kawanishi.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z